PATHOGENIC ESCHERICHIA COLI BACTERIA INFECTION IN LANDRACE PIGLETS IN ANTIGA KELOD, MANGGIS, KARANGASEM - Yolla Noviolita; I Gusti Ketut Suarjana; Ida Bagus Oka Winaya; Ida Bagus Made Oka; Ida Bagus Kade Suardana (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Colibacillosis is a disease caused by pathogenic Escherichia coli bacteria. Infected piglets experience weight loss, stunted growth and if not treated immediately will cause death. A 16-day-old Landrace piglet died with clinical signs of weakness and yellowish white diarrhoea for 4 days. The farmer's population was 25 pigs. Epidemiology showed morbidity of 8%, mortality of 4%, and case fatality rate of 50%. Anatomical pathology examination revealed distended intestines with bleeding and hyperaemic lungs. Bacterial culture of lung and intestinal organs showed positive results of gram-negative Escherichia coli bacteria. The results of parasitological examination of native, sedimentation and floating methods were negative for protozoan and helminth infections. Histopathology showed congestion, haemorrhage and neutrophil-dominated inflammatory cell infiltration in the intestines and lungs, while the brain, heart and liver were congested. Based on all laboratory examination results, the case pig was diagnosed with colibacillosis. Improved sanitation and biosecurity of the barn and barn environment needs to be routinely carried out.